“Nossa energia tem um Norte”: propostas e (des) encontros no planejamento energético na Amazônia Oriental - Andrey Minin Martin (Confins)
The Northern region of Brazil has historically stood out as a space with natural potential that has always awakened public and private concerns regarding the exploitation of resources and recently the development of large projects. From the extraction of latex to current mining projects, as in the Grande Carajás project, these ventures have been seen as imperative to establish new conditions of integration and even improvements for the northern part of the country. Together, a new force intensified from the second half of the twentieth century as an element and central pillar so that all these undertakings could be realized. Energy production thus became a goal and synonymous with exploiting the potential of the Amazon, entering complacent spaces and producing new narratives about this region. This article proposes to debate how transformations occurred between the planning process and a non-existent structuring of this sector in the Eastern Amazon. Taking as a motto the documentary production of companies involved in this process, such as Eletronorte, Celpa and Eletrobrás, as well as by observing the debates that permeated government media and speeches, the article seeks to bring subsidies to understand how the paths followed by these projects, from the present to the past , are apprehended as dynamic elements of a region, but that historically have not consolidated a real execution focused on the interests and needs of this space.